2015
DOI: 10.1007/s11126-015-9369-z
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Marijuana Risk Perception in a Population of Substance Abusing Patients

Abstract: Risk perception has been shown to be protective with regard to marijuana use. Notably, the risk perception of marijuana in individuals with substance abuse problems varies significantly from that of the general public. Understanding how risk perception is formed in substance users could explain these differences and help predict the consequences of policy changes. Using this framework, we explored risk perception and its formation in a sample of substance abusing veterans. Semi-structured interviews were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
2
18
0
1
Order By: Relevance
“…Using a qualitative research approach, Wilkinson and colleagues interviewed a group of 31 veterans treated for substance use disorders (including cannabis use disorder) about their attitudes toward cannabis. Semi-structured interviews revealed that these participants emphasized the role of individual experience on the formation of cannabis risk perception (11). Other factors, such as information-based programs, medical professionals and the popular media seem to bear less influence on attitude formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a qualitative research approach, Wilkinson and colleagues interviewed a group of 31 veterans treated for substance use disorders (including cannabis use disorder) about their attitudes toward cannabis. Semi-structured interviews revealed that these participants emphasized the role of individual experience on the formation of cannabis risk perception (11). Other factors, such as information-based programs, medical professionals and the popular media seem to bear less influence on attitude formation.…”
Section: Discussionmentioning
confidence: 99%
“…That is, the association between risk perception and use may arise in part because those who do not experience adverse consequences from cannabis use are likely to modify their risk perception. In fact, results from qualitative studies have shown that the perceived risk of cannabis use is reportedly inferred, to a large extent, from individual experience with use (10,11). That is, if the experience is generally positive, cannabis is regarded as a low-risk drug.…”
Section: Introductionmentioning
confidence: 99%
“…Veteran advocacy groups have been created to further veterans’ rights to access cannabis for medical (MC) purposes and discuss its use with their VHA providers (for e.g., “http://www.vetscp.org/#,” 2017). There are also published reports that veterans perceive cannabis to be a low-risk or safe substance unlike other drugs of abuse (Wilkinson, van Schalkwyk, Davidson, & D’Souza, 2016) and expect cannabis to provide relief from symptoms of combat-related trauma (Earleywine & Bolles, 2014). However, there has been little research on the patterns and correlates of MC use specifically among veterans.…”
Section: Introductionmentioning
confidence: 99%
“…Those with marijuana use disorder may be cognizant of marijuana's negative effects on their life. Given their higher rates of alcohol and nicotine use disorders and DUI, those with marijuana use disorder may also perceive the negative effects of polysubstance use, including more harmful substances (Wilkinson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Marijuana use has also been found to contribute to incrementally lower risk perceptions among adolescents over time, showing a possible reappraisal of risk perception among users (Grevenstein et al, 2015). A qualitative study of marijuana risk perception formation among substance using veterans (aged 24-65 years) also found that (1) these adults based their risk perceptions on personal experience rather than scientific knowledge; (2) a majority viewed marijuana as significantly different from other drugs because they saw it as safe, nonaddictive, lacking physical withdrawal symptoms, and as having less overt behavioral effects; and (3) only a minority recognized marijuana's capacity to cause negative social consequences; act as a precursor to other, more harmful substance use; and cause paranoia or worsen psychosis (Wilkinson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%